Application of the Problem Based Learning Learning Model to Increase Student Activity and Learning Outcomes in Learning Food Quality Testing at SMK SMTI Makassar - Nurwahidaya; Jamaluddin P; Ratnawaty Fadillah (Formosa Journal of Applied Sciences, 2023)
This research is a classroom action research that aims to determine the increase in student activity and learning outcomes in learning food quality testing for class XI PM 3 SMK SMTI Makassar. The independent variable in this study is the application of the problem-based learning model while the dependent variable is the activity and learning outcomes. The population in this study were SMKN 9 Makassar and SMK SMTI Makassar, while the sample was class XI PM 3 SMK SMTI Makassar for the 2021/2022 academic year with a total of 28 students. This research was conducted in two cycles. Cycle I carried out the stages of planning, implementation, observation and reflection, as well as cycle II which was carried out with the same stages in cycle I. The results showed that there was a significant increase in student activity and learning outcomes. Judging from the quantitative analysis which shows the activeness and learning outcomes of students increased.